PURα Promotes the Transcriptional Activation of PCK2 in Esophageal Squamous Cell Carcinoma Cells - Sun, Yan (Genes (Basel), 2020)
Esophageal squamous cell carcinoma (ESCC) is one of the most lethal gastrointestinal malignancies due to its characteristics of local invasion and distant metastasis. Purine element binding protein α (PURα) is a DNA and RNA binding protein, and recent studies have showed that abnormal expression of PURα is associated with the progression of some tumors, but its oncogenic function, especially in ESCC progression, has not been determined. Based on the bioinformatic analysis of RNA-seq and ChIP-seq data, we found that PURα affected metabolic pathways, including oxidative phosphorylation and fatty acid metabolism, and we observed that it has binding peaks in the promoter of mitochondrial phosphoenolpyruvate carboxykinase (PCK2). Meanwhile, PURα significantly increased the activity of the PCK2 gene promoter by binding to the GGGAGGCGGA motif, as determined though luciferase assay and ChIP-PCR/qPCR. The results of Western blotting and qRT-PCR analysis showed that PURα overexpression enhances the protein and mRNA levels of PCK2 in KYSE510 cells, whereas PURα knockdown inhibits the protein and mRNA levels of PCK2 in KYSE170 cells. In addition, measurements of the oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) indicated that PURα promoted the metabolism of ESCC cells. Taken together, our results help to elucidate the molecular mechanism by which PURα activates the transcription and expression of PCK2, which contributes to the development of a new therapeutic target for ESCC.